Dark-matter-free dwarf galaxy formation at the tips of the tentacles of jellyfish galaxies - Lora, Verónica; Smith, Rory; Fritz, Jacopo; Pasquali, Anna; Raga, Alejandro C. (The astrophysical journal, 2024)
When falling into a galaxy cluster, galaxies experience a loss of gas due to ram pressure stripping. In particular, disk galaxies lose gas from their disks, and very large tentacles of gas can be formed. Because of the morphology of these stripped galaxies, they have been referred to as jellyfish galaxies. It has been found that star formation is triggered not only in the disk, but also in the tentacles of such jellyfish galaxies. The observed star-forming regions located in the tentacles of those galaxies have been found to be as massive as 3 × 107 M ⊙ and with sizes >100 pc. Interestingly, these parameters in mass and size agree with those of dwarf galaxies. In this work, we make use of the state-of-the-art magnetohydrodynamic (MHD) cosmological simulation IllustrisTNG-50 to study massive jellyfish galaxies with long tentacles. We find that, in the tentacles of TNG-50 jellyfish galaxies, the star formation regions (gas+stars) formed could be as massive as ∼2 × 108 M ⊙. A particular star-forming region was analyzed. This region has a star formation rate of 0.04 M ⊙ yr−1, it is metal-rich, has an average age of 0.46 Gyr, and has a half-mass radius of ∼1 kpc, typical of standard dwarf galaxies. Most importantly, this region is gravitationally self-bound. Overall, we identify a new type of dwarf galaxy being born from the gas tentacles of jellyfish galaxies that, by construction, lacks a dark matter halo.